Strategi Public Relations Dalam Membangun Brand Image Melalui Media Sosial Pada Afsha Official - Choerotun Nisa, Arriza Indah; Susanto, Tri (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
This study aims to determine the public relations strategy in building brand image through Instagram social media at Afsha Official. This research uses a qualitative approach with a constructivism paradigm. Using the Case Study method, and data collection techniques by means of interviews, observation and documentation. Based on the results of this study, it discusses the public relations strategy in building brand image through Instagram social media at Afsha Official which is carried out by the marketing and business development division. The strategy that is carried out refers to the theory of public relations mix from Thomas L. Harris, namely publication, events, community involvement, information or image, lobbying and negotiation, and social responsibility. Research Contribution, namely the discussion in this journal focuses on the Public Relations Mix strategy at the religious equipment company, namely Afsha Official, so that the problems at that location are different from other locations that have been studied. Penelitian ini bertujuan untuk mengetahui strategi pubic relations dalam membangun brand image melalui media sosial instagram pada Afsha Official. Penelitian ini menggunakan pendekatan kualitatif dengan paradigma konstruktivisme. Menggunakan metode studi kasus, dan teknik pengumpulan data dengan cara wawancara, observasi dan dokumentasi. Hasil penelitian ini membahas strategi public relations dalam membangun brand image melalui media sosial Instagram pada Afsha Official yang dilakukan oleh Divisi Marketing dan Business Development. Strategi yang dijalankan mengacu pada teori Bauran Public Relations dari Thomas L. Harris yaitu publikasi, program acara, membuat berita, hubungan dengan komunitas, menginformasikan atau memberitahukan citra, lobi dan negosiasi, dan tanggung jawab sosial. Kontribusi Penelitian yaitu pembahasan pada jurnal ini berfokus pada strategi Bauran Public Relations di Perusahaan alat ibadah yaitu Afsha Official sehingga permasalahan di lokasi tersebut berbeda dengan lokasi lain yang sudah pernah diteliti.